Gêneros e formatos da folkcomunicação - Gobbi, Maria Cristina [UNESP] (My University, 2014)
The study of Folk Communication is a major legacy of Luiz Beltrão in his endeavor to educate journalism students about collective communication and its many ramifications. The topicality of this pioneering research has piqued the interest of many groups, not only in Brazil but also in Latin America and in European countries. This research seeks to know, map, and organize the data on Folk Communication available on the web, dealing more specifically with Iconic Folk Communication, Funeral Format, and Kinetics Folk Communication, Format: Rite of Passage, as defined by Professor José Marques de Melo in his investigation on Genres and Formats of Folk Communication: a taxonomic approach. Employing bibliographic and documentary research, the objective of this analysis is to verify which types are present, and whether there are other formats and identify them.

O estudo sobre a Folkcomunicação foi um dos principais legados de Luiz Beltrão em sua batalha para conscientizar os estudantes de jornalismo a respeito da comunicação coletiva e de seus múltiplos desdobramentos. A atualidade da pesquisa desse pioneiro tem despertado o interesse de diversos grupos, não só no Brasil, mas também na América Latina e em países europeus. A pesquisa que ora realizamos busca conhecer, mapear, sistematizar os dados que estão sendo disponibilizados na rede mundial sobre Folkcomunicação, tratando mais especificamente da Folkcomunicação Icônica, Formato Funerário e da Folkcomunicação Cinética, Formato: Rito de Passagem, conforme definiu o professor José Marques de Melo em seu trabalho sobre Gêneros e Formatos Folkcomunicacionais: aproximação taxionômica. Utilizando pesquisa bibliográfica e documental, a análise objetiva verificar que tipos estão presentes e se há outros formatos e quais são eles.
Keywords: Folkcommunication; Luiz Beltrão; Communication research; Latin America; Genres and formats; Folkcomunicação; Luiz Beltrão; Pesquisa em comunicação; América Latina; Gêneros e formatos